Thermalization dynamics of a gauge theory on a quantum simulator - Zhou, Zhao-Yu; Su, Guo-Xian; Halimeh, Jad C.; Ott, Robert; Sun, Hui; Hauke, Philipp; Yang, Bing; Yuan, Zhen-Sheng; Berges, Jürgen; Pan, Jian-Wei (Arxiv, 2021)
Gauge theories form the foundation of modern physics, with applications ranging from elementary particle physics and early-universe cosmology to condensed matter systems. We demonstrate emergent irreversible behavior, such as the approach to thermal equilibrium, by quantum simulating the fundamental unitary dynamics of a U(1) symmetric gauge field theory. While this is in general beyond the capabilities of classical computers, it is made possible through the experimental implementation of a large-scale cold atomic system in an optical lattice. The highly constrained gauge theory dynamics is encoded in a one-dimensional Bose--Hubbard simulator, which couples fermionic matter fields through dynamical gauge fields. We investigate global quantum quenches and the equilibration to a steady state well approximated by a thermal ensemble. Our work establishes a new realm for the investigation of elusive phenomena, such as Schwinger pair production and string-breaking, and paves the way for more complex higher-dimensional gauge theories on quantum synthetic matter devices.